The secret theory of drawing. - Mac Giolla Léith, Caoimhin (London : The Drawing Room London, 2006)
Austen, David ; Donnelly, Trisha ; Eliasson, Olafur ; Floyer, Ceal ; Gallagher, Ellen ; Gonzalez-Foerster, Dominique ; Gordon, Douglas ; Ireland, Patrick ; Johnston, Alan ; Latham, John ; Manders, Mark ; Mullican, Matt ; Sala, Anri ; Sarcevic, Bojan ; Tuerlinckx, Joëlle ; Wilkes, Cathy
biog. 2 p.
Engels
Exhibition. The secret theory of drawing (1). The Drawing Room London. 05.10.2006 - 19.11.2006. Exhibition. The secret theory of drawing (2). Model Arts & Niland Gallery Sligo. 27.01.2007 - 18.03.2007.
boek